Post-diagnostic C-reactive protein and albumin predict survival in Chinese patients with non-small cell lung cancer: a prospective cohort study - Jin-Rong Yang (Nature Portfolio, 2019)
Abstract Non-small cell lung cancer (NSCLC) is the most commonly diagnosed lung cancer and is associated with poor prognosis. This study aimed to analyze if serum C-reactive protein (CRP), albumin (Alb), and CRP/Alb ratio could provide prognostic information in patients with NSCLC. 387 patients with primary NSCLC were included in this analysis. Cox proportional hazards regression was used to estimate hazard ratio (HR) and 95% confidence interval (CI) of death with adjustment for some potential confounders. The multivariate regression analyses revealed the statistically significant associations of decreased survival of patients with NSCLC with elevated CRP, decreased Alb, and elevated CRP/Alb ratio. The HRs of mortality were 1.56 (95% CI: 0.80–3.04) and 2.64 (95% CI: 1.35–5.16) for patients in the second and the highest tertiles of CRP (P-trend = 0.003). For albumin, the HR was 0.50 (95% CI: 0.29–0.85) for the normal group. The CRP/Alb ratio strongly predicted the survival of patients in the highest tertile with a fourfold risk of dying compared with those in the lowest tertile (HR = 4.14, 95% CI: 2.15–7.98). The subgroup analysis according to various patient characteristics confirmed these associations. In conclusion, serum CRP, albumin, and CRP/Alb ratio are predictive of survival for Chinese patients with NSCLC.